How contact foraging experiences affect preferences for host-related odors in the larval parasitoid Cotesia marginiventris (Cresson) (Hymenoptera: Braconidae) - Turlings, Ted; Scheepmaker, J. W. A.; Vet, Louise E. M.; Tumlinson, James H.; Lewis, W. Joe (My University, 1990)
Responses of individual females of the parasitoid Cotesia marginiventris to the odors of four different complexes of host larvae feeding on leaves were observed in a four-arm olfactometer. The plant-host complexes were composed of fall armyworm (FAW) larvae or cabbage looper (CL) larvae feeding on either corn or cotton seedlings. Prior to testing, each female was given a brief foraging experience on a plant-host complex and was then exposed to the odors of the same complex in the olfactometer. The experienced females responded to familiar odors in a dose-related manner, and these responses were virtually identical to all four complexes. Preferences for the odors of one of two plant-host complexes were tested in dual choice situations. Generally, FAW odors were preferred over CL odors and corn odors over cotton odors. A short foraging experience significantly affected the females' odor preferences in favor of the odors released by the experienced complex. Additional experiments revealed that neither longer bouts of experience nor bouts that included ovipositions resulted in a stronger change in preference. Experience affected preference in combinations where only the host species was varied as well as in combinations where only the plant species was varied. The results, therefore, strongly indicate that both the plants and the hosts somehow are involved in the production and/or release of the semiochemicals that attract C. marginiventris.
Keywords: Hymenoptera - Braconidae - Cotesia marginiventris - host-finding - semiochemicals - conditioning